The Language Policy and the Linguistic Rights in Syria: The Kurdish Language a Pattern - SULAIMAN, MOHAMMAD ISSA (İstanbul Kültür Üniversitesi, 2022)
Language policy is a tool for regulating State-building and allocating resources among different language groups. However, in some countries with ethnic-language groups, the language policy is a source of conflicts between language groups and the state because of its symbolic value for the ethnic groups. The attitude of language groups towards the language policy in the state is shaped by their comprehension of language policy and their relations with the state; therefore, those language groups head for perceive Language in different ways as well, and they have different demands, with different demands, with different paths. This study investigates the Kurdish situation in Syria from a language perspective. Syria has been conflict-stricken since 2011. This conflict is partially in the policy of the ruling ethnic majority, being practised since the establish the country after WWI against the minority. This policy's best manifestation has been in the language domain, where the state has adopted various assimilatory strategies against ethnic minority groups, chief among which has been the Kurdish community. The Kurds are an ethno-language group whose citizenship has often been previously questionable. As a result, the Syrian state's language policy has led to tripled minoritization and oppression of the Kurds. Therefore, my study will prove vital to understanding the state's assimilatory strategies in the domain of language in a multiethnic polity such as Syria. My paper will study the Kurdish language status in Syria in creating the national identity for Kurds in Syria. Also, it will attend to the government's sociolinguistic and Language policies and planning. Through this study, I will investigate the state documents (Constitutions, Decrees, internal status for government institutions, and organizations), the publications released by Kurds in Syria and interviews with the representatives of Kurds in Syria. Further, the study will investigate the linguistics justice from the human rights approach and the issue of protecting minority languages and linguistic diversity in establishing a democratic system in Syria. Broadly, the Kurdish groups view the language policy as a question of recognition, and they demand that their language be given the same status as the Arabic language. In order to satisfy the demands and interests of this linguistic group, any future policymakers in Syria should take these into account when creating language policies.
Suriye'de Dil Politikası ve Dil Hakları: Kürt Dili Bir Örnek
▪ Yüksek lisans tezi.
Keywords: Syria; Kurds; Kurdish Language; Language Rights; Linguicide; Liberalism